Optimizing the Legal Status of the National Sharia Arbitration Board as a Non-Litigation Institution for Sharia Economics in Indonesia - Cahaya Permata; Mhd. Yadi Harahap; Ramadhan Syahmedi Siregar; Iwan Iwan (Universitas Islam Negeri Sumatera Utara, 2025)
The development of the Islamic economy and finance in Indonesia has led to an increasing need for dispute resolution mechanisms that are effective, efficient, and compatible with Sharia principles. Badan Arbitrase Syariah Nasional (Basyarnas) functions as a non-litigation dispute resolution institution in the field of Islamic economics. This study aims to examine the legal standing of Basyarnas within the national legal system and to analyze strategies for optimizing its role as an out-of-court forum for resolving Islamic economic disputes. Based on a normative juridical review employing statutory and conceptual approaches, and secondary data collected through document analysis, This study finds that the legal existence and strategic role of Basyarnas continue to face various challenges, including the weak recognition of its decisions by judicial institutions, the low level of business actors? literacy regarding Sharia arbitration mechanisms, and limitations in human resources and institutional infrastructure. Therefore, it is necessary to strengthen the regulatory framework governing the legal standing of Basyarnas as a dispute resolution institution, enhance inter-institutional harmonization, improve the competence of Sharia arbitrators, and promote the digitalization of arbitration services as strategic measures to reinforce Basyarnas?s role as an integral part of the Islamic economic dispute resolution system in Indonesia.